2016
DOI: 10.21608/adjalexu.2016.58053
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Study of the Effect of Zinc Oxide Nanoparticles on Rat Parotid Salivary Glands and the Protective Role of Quercetin

Abstract: INTRODUCTION:Nanotechnology is the technology of diagnosing, treating, and preventing diseases using nanoscale structured materials. Zinc oxide nanoparticles (ZnO NPs) have useful effects for their less environmental hazards and for their application usages: tooth pastes, biomedicine and food as zinc supplements. On the other hand, ZnO NPs have toxic effect due to their tissue accumulation ability. Quercetin (Qc) is an antioxidant, categorized as a flavonol. Its beneficial effects are attributed to its phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Our results might refer to the accumulation of large amount of Zn in the heart tissue. This finding is supported by Hamza et al and Kermanshahi et al who exhibited that the absorption rate of ZnONPs at a dose of 300 mg/kg is high in the heart tissue of female mice. Besides, the result is in line with the prior studies in which the toxicity of ZnO‐NPs might result directly from the NPs themselves or from Zn +2 ions released either after cellular uptake or the intracellular dissolution leading to OS, mitochondrial dysfunction and cardiovascular damage .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our results might refer to the accumulation of large amount of Zn in the heart tissue. This finding is supported by Hamza et al and Kermanshahi et al who exhibited that the absorption rate of ZnONPs at a dose of 300 mg/kg is high in the heart tissue of female mice. Besides, the result is in line with the prior studies in which the toxicity of ZnO‐NPs might result directly from the NPs themselves or from Zn +2 ions released either after cellular uptake or the intracellular dissolution leading to OS, mitochondrial dysfunction and cardiovascular damage .…”
Section: Discussionsupporting
confidence: 60%
“…Our results might refer to the accumulation of large amount of Zn in the heart tissue. This finding is supported by Hamza et al 61 and Kermanshahi et al 54 who exhibited that the absorption rate of ZnONPs at a dose of 300 mg/kg is high in the heart tissue of female mice.…”
Section: Discussionsupporting
confidence: 58%
“…The vacuolization reflected cellular swelling that may be caused by failure of the energy-dependent Na + -K + ion pumps in the plasma membranes. Lipid peroxidation, accumulation of Na + intracellularly, and progressive osmolarity changes with a consequent entry of water into the cells could account for those observations (Hamza et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These studies had shown complete inhibition of submandibular secretory function including the total proteins and calcium beside the declined salivary flow rate. These foregoing observations could be related to the previously mentioned damaging effect of oxidative stress produced by CPFX® on nuclei "that results in pleomorphism, chromatin condensation, and karyolysis in addition to the role played by oxidative stress in degeneration of RER, mitochondria, and Golgi complex that negatively affect protein synthesis pathway (Hamza et al, 2016). Mercury bromophenol stain of CIN group in our study showed mild staining for total proteins in acini but moderate to strong staining in GCT, modertae in SD and mild to moderate in ED.…”
Section: Discussionmentioning
confidence: 96%